The megalithic tombs in the region of Belas (Sintra, Portugal) and their aesthetic manifestations - Cardoso, João Luís (2014)
Within the region of Lisbon, artistic manifestations from megalithic tombs are virtually unknown, although they are frequent in other regions. The megalithic group of Belas has a particular relevance to this subject given its two types of aesthetic and artistic features already published by previous authors, but not properly emphasized or characterized. On one hand, the builders of the three known tombs –Pedra dos Mouros, Monte Abraão and Estria– made selective usage of certain types of rock slabs, based on their morphological characteristics on the slab surfaces, structuring them within an intentional aesthetic pattern. On the other hand, on the external surface of one of the slabs of Pedra dos Mouros, two engraved anthropomorphic fi gurines are known, but need to be reevaluated taking into account the most recent studies.